Abstract art and communication in 'Mamluk' architecture - Jakeman, J; Jakeman, Jane (1993)
﻿ Fourteenth-century Cairo saw a movement towards abstract, geometric art. This movement reflected contemporary intellectual interests and represents the culmination of the ascendancy of Islamic philosophy over the humanist vocabulary of art. The thesis seeks explanations for the positive, i.e. for the forms which art actually took, rather than concentrating on prohibitive mechanisms. In architecture, the disappearance of stucco vegetal decoration may have been partly due to the effects of an outbreak of plague, but the main influences on contemporary art and architecture came from the esoteric habits of thought induced by sufism, alchemy and hermeticism, and from the dualist concerns of Islamic philosophy. The thesis discusses the continuity between sufism and Shī'ism, the history of sufism in Cairo as it affected art and architecture, concepts of the microcosm and the macrocosm, and theories of colour, substance and gilding. The thesis examines talismans and other esoteric material. It discusses architectural incorporata, presents a catalogue of Pharaonic material re-used in Islamic architecture, and argues that blocks bearing Pharaonic hieroglyphs represented Hermetic lore and, at entrances to buildings, paralleled the use of Pharaonic references at the beginning of esoteric manuscripts. The detailed discussion of architecture takes the form of an examination of a religious building, scrutinising the underlying principles of decoration and then moving on to specific elements such as the entrance and the mihrab. The thesis discusses, and dissents from, iconographic interpretations of architectural imagery. It attempts to evolve a terminology for discussion and concludes that 'mamluk' is inappropriate as a cultural term, since the influence of the individual patron on art and architecture was less innovative than the intellectual background of the period, and the dissociation of the patron from contemporary society has been over-estimated. It comes to the conclusion that 'an art of the bāṭin* would more effectively express the major influence on the art and architecture of fourteenthcentury Cairo.